Jurgen Dobereiner: a life dedicated to science - Dutra, Iveraldo S. [UNESP]; Colling, Axel; Driemeier, David; Brito, Marilene F.; Ubiali, Daniel G.; Schild, Ana Lucia; Riet-Correa, Franklin; Barros, Claudio S. L. (Revista Pesquisa Veterinaria Brasileira, 2019)
Dr. Jurgen Dobereiner was born in Germany, on the 1st of November 1923, and lived in Brazil for 68 years during which time he developed a range of scientific projects in veterinary pathology and related disciplines. His main interests were the identification of new poisonous plants and mineral deficiencies and the causes of cara inchada (swollen face a periodontal disease) and botulism in livestock. This research has resulted in the improved health and saving of hundreds of thousands of animals, mainly cattle, annually, and is consequently of enormous economic value to the country. This contribution remains largely under appreciated. He was also involved in organizing diagnostic methods for identifying infectious diseases such as African swine fever and glanders in horses. One of his other major achievements has been the foundation and editing of specialized scientific journals for the documentation of veterinary science research results. At the beginning of his career in the 1950s, he and colleagues from the Institute for Animal Biology (IBA) were struggling to find a national scientific journal where research results from veterinary medicine could be published with practical application to the Brazilian reality. In consequence, the team founded Arquivos do Instituto de Biologia Animal and published three volumes (1959-1961). He then founded and edited Pesquisa Agropecuaria Brasileira (The Brazilian Journal of Agricultural Research) that included a veterinary section. A series of veterinary volumes were published (1966-1976). Finally, in 1978 he helped create the Brazilian College of Veterinary Pathology (CBPA) that published Pesquisa Veterinaria Brasileira (The Brazilian Journal of Veterinary Research) from 1981. The main goal was to communicate the most relevant disease problems of Brazilian livestock, in particular pathology and related subjects such as epidemiology, clinical study series and laboratory diagnosis to field veterinarians and academics. Dr. Jurgen Dobereiner was president of CBPA (1978-2018) and chief editor of Pesquisa Veterinaria Brasileira (1981-2018). He passed away on the 16th of October, 2018, at the age of 94 at his home in Seropedica/RJ, Brazil.
Keywords: Science; livestock diseases; diagnosis; veterinary pathology; poisonous plants; mineral deficiencies; periodontal disease; botulism